2018
DOI: 10.1186/s13568-018-0549-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long-term fertilization strategies on bacterial community composition in a 35-year field experiment of Chinese Mollisols

Abstract: Bacteria play vital roles in soil biological fertility; however, it remains poorly understood about their response to long-term fertilization in Chinese Mollisols, especially when organic manure is substituted for inorganic nitrogen (N) fertilizer. To broaden our knowledge, high-throughput pyrosequencing and quantitative PCR were used to explore the impacts of inorganic fertilizer and manure on bacterial community composition in a 35-year field experiment of Chinese Mollisols. Soils were collected from four tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 77 publications
(89 reference statements)
4
22
0
Order By: Relevance
“…Several studies have proven that fertilization strategies have an impact on the genetic diversity of soil microbial communities [83][84][85]. Our study revealed that the application of mineral fertilizer enriched with beneficial bacterial strains increased the number of 16S rDNA OTU's in BA soil and ITS1 OTU's for both soil types.…”
Section: Discussionmentioning
confidence: 49%
“…Several studies have proven that fertilization strategies have an impact on the genetic diversity of soil microbial communities [83][84][85]. Our study revealed that the application of mineral fertilizer enriched with beneficial bacterial strains increased the number of 16S rDNA OTU's in BA soil and ITS1 OTU's for both soil types.…”
Section: Discussionmentioning
confidence: 49%
“…Only rarely detected lower taxons were different between the soils. From the genera that were present in significantly different quantities (higher in conventional farming), Sphingomonas and Gemmatimonas were observed previously to be increased in farming with mineral fertilizers (Ma et al, 2018). We also found Rhodanobacter genus, which was previously connected with denitrification of soil (Green et al, 2012), present only in conventional farming soil (0.37% relative abundance) and absent from organic farming soil.…”
Section: Discussionmentioning
confidence: 92%
“…In this work, at the phylum level, Proteobacteria firstly dominated in all the soil samples, probably due to a wide range of complex organic molecules can be utilized by the members of this phylum [46]. Because the members of phylum Proteobacteria have been reported to facilitate the horizontal transfer of genes related to photosynthesis, its high abundance is particularly vital for crop growth [47]. Furthermore, many taxa within this phylum exhibit disease-suppression activity, such as defending plant roots from fungal pathogen infection, which may improve the health of plant and soil [27].…”
Section: Effects Of Straw Input On Microbial Community Compositionmentioning
confidence: 84%
“…The result of Banerjee et al (2016) indicated that the Acidobacteria and Gemmatimonas were the keystone taxa during organic matter decomposition in an arable soil, and these taxa were importance in carbon turnover [20]. Ma et al (2018) reported that the Acidobacteria increased with the decline of soil pH, when in the fertilizer rich regime [47]. In the current study, Acidobacteria formed the second largest group but was lower in SC, SD and BC samples compared to CK (Figure 2(a)), suggesting the improvement of soil nutrition and deacidification effect by straw incorporation or BC addition.…”
Section: Effects Of Straw Input On Microbial Community Compositionmentioning
confidence: 99%
See 1 more Smart Citation